If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + ln(x + 2) = 8 Multiply ln * x lnx + ln(x + 2) = 8 Reorder the terms: lnx + ln(2 + x) = 8 lnx + (2 * ln + x * ln) = 8 lnx + (2ln + lnx) = 8 Reorder the terms: 2ln + lnx + lnx = 8 Combine like terms: lnx + lnx = 2lnx 2ln + 2lnx = 8 Solving 2ln + 2lnx = 8 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -8 + 2ln + 2lnx = 8 + -8 Combine like terms: 8 + -8 = 0 -8 + 2ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + ln + lnx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + ln + lnx)' equal to zero and attempt to solve: Simplifying -4 + ln + lnx = 0 Solving -4 + ln + lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '4' to each side of the equation. -4 + ln + 4 + lnx = 0 + 4 Reorder the terms: -4 + 4 + ln + lnx = 0 + 4 Combine like terms: -4 + 4 = 0 0 + ln + lnx = 0 + 4 ln + lnx = 0 + 4 Combine like terms: 0 + 4 = 4 ln + lnx = 4 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 11=5*y-4 | | xy=15x^2 | | (2x-8)*(x+3)=0 | | 15=13+2x | | 5-2x=3-14x | | 16e-32=176 | | 9*b+5=23 | | 4(-4p+4)+6p= | | 7(-7x-1)=336 | | 1/2*?(x)=1 | | 2+7+X=6+3 | | 1.4-16(t+6)=4.6 | | (-3)(7)+(-3)(3)= | | 1/2?(x)=1 | | 3(2x+6)=0 | | 1/2?x=1 | | 50+.10t=10+.40t | | =(x^70)(sin*(8*x)) | | -10k-7(5-9k)= | | 7.2=-5x^2+12x | | -19k-7(5-9k)= | | 43s+.10=.40+30s | | =16(4) | | =50*cos(7*x^7) | | (-3)(4x)= | | 12x+24=26 | | 16+x=66 | | -06(r+0.2)=1.8 | | y=-5x^2+12x | | =4+120-64 | | 3(30+1.5y)+3y=60 | | =50cos(7x^7) |